Regulation of microtubule nucleation in mouse bone marrow-derived mast cells by ARF GTPase-activating protein GIT2 - Sulimenko, Vadym; Sládková, Vladimíra; Sulimenko, Tetyana; Dráberová, Eduarda; Vosecká, Věra; Dráberová, Lubica; Skalli, Omar; Dráber, Pavel (Frontiers in Immunology, 2024)
Aggregation of high-affinity IgE receptors (FcεRIs) on granulated mast cells triggers signaling pathways leading to a calcium response and release of inflammatory mediators from secretory granules. While microtubules play a role in the degranulation process, the complex molecular mechanisms regulating microtubule remodeling in activated mast cells are only partially understood. Here, we demonstrate that the activation of bone marrow mast cells induced by FcεRI aggregation increases centrosomal microtubule nucleation, with G protein-coupled receptor kinase-interacting protein 2 (GIT2) playing a vital role in this process. Both endogenous and exogenous GIT2 were associated with centrosomes and γ-tubulin complex proteins. Depletion of GIT2 enhanced centrosomal microtubule nucleation, and phenotypic rescue experiments revealed that GIT2, unlike GIT1, acts as a negative regulator of microtubule nucleation in mast cells. GIT2 also participated in the regulation of antigen-induced degranulation and chemotaxis. Further experiments showed that phosphorylation affected centrosomal localization of GIT2, and that during antigen-induced activation, GIT2 was phosphorylated by conventional protein kinase C, which promoted microtubule nucleation. We propose that GIT2 is a novel regulator of microtubule organization in activated mast cells by modulating centrosomal microtubule nucleation. Abbreviations: Ab(s), antibody(ies); Ag, antigen; BMMCs, bone marrow-derived mast cell; BMMCL, bone marrow-derived mast cell line; cPKCs, Ca 2+and diacylglycerol-regulated conventional protein kinases C; DNP, dinitrophenyl; FcRI, high affinity IgE receptor; Fura-2-AM, Fura-2 acetoxymethyl ester; GCP, γ-tubulin complex protein; GIT, G protein-coupled receptor kinaseinteracting protein; mAb(s), monoclonal antibody(ies); MAP, microtubule-associated protein; PAK, p21 protein (Cdc42/Rac)-activated kinase 1; PIX, p21-activated kinase interacting exchange factor; phorbol 12-myristate 13-acetate (PMA); SP, substance P; γTuRCs, γ-tubulin ring complexes.